2015
DOI: 10.1080/10668926.2014.942894
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Design Practices of a Vocational Community College in a Developing Context: Challenges and Needs

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis. The accuracy of the Content s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The three domains are as follows: 1 À the curriculum development domain, concerning the technical curriculum development tasks and activities that academic managers need to work on with others; 2 À the administrative domain, referring to the routine administrative tasks that keep the educational process running; and 3 À the leadership domain, concerning leadership roles and practices expected of academic managers if they are to perform effectively in the other two domains. Of these three domains, the curriculum development domain is the one least attended to by college middle management for several reasons, one of which is the lack of professional support (Albashiry et al, 2015;Nguyen, 2012;Stark et al, 2002;Wolverton, Ackerman, & Holt, 2005). The current study reports on the design and effects of a professional development arrangement (PDA) that focused on improving middle managers' learning about curriculum development, so that they could better lead the curriculum development tasks associated with the curriculum development domain.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The three domains are as follows: 1 À the curriculum development domain, concerning the technical curriculum development tasks and activities that academic managers need to work on with others; 2 À the administrative domain, referring to the routine administrative tasks that keep the educational process running; and 3 À the leadership domain, concerning leadership roles and practices expected of academic managers if they are to perform effectively in the other two domains. Of these three domains, the curriculum development domain is the one least attended to by college middle management for several reasons, one of which is the lack of professional support (Albashiry et al, 2015;Nguyen, 2012;Stark et al, 2002;Wolverton, Ackerman, & Holt, 2005). The current study reports on the design and effects of a professional development arrangement (PDA) that focused on improving middle managers' learning about curriculum development, so that they could better lead the curriculum development tasks associated with the curriculum development domain.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A previous exploratory study (Albashiry et al, 2015) identified several college-wide sub-standard curriculum development practices jeopardising the college programmes' external consistency (i.e. relevance of the programmes to the external stakeholders' expectations) and internal consistency (i.e.…”
Section: Study Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…It is usually the academic managers at the middle level of these institutions (e.g., academic departments) who are expected to play a critical role in maintaining and enhancing the quality and relevance of TVET programs (Albashiry, Voogt, & Pieters, 2015;Boateng, 2012b;Mazani, 2013). In practice, however, pre-and in-service professional development opportunities for TVET program managers are reported to be scarce; as a consequence, Heads of Department (HoDs) in tertiary TVET institutions have been found to lack adequate competency in leading effective curriculum development practices, resulting in academic departments that do not have goals, and curricula that have not been reviewed for many years (Albashiry et al, 2015;Bakah et al, 2012a;Gervedink Nijhuis et al, 2012;Mazani, 2013).…”
Section: Introductionmentioning
confidence: 99%